Determining the Role of Rural Women in Decision Making Related to Farm Activities in Burdwan, West Bengal, India - Pal , Subhadip (Current Aspects in Business, Economics and Finance Vol. 5, 2022)
The present study was conducted to find out the participation and decision making of rural households in various farming activities. Women play crucial and significant role in farm activities. This study analysed women’s participation and decision making process in farming activities in Katwa Block- I of Burdwan district, India. Most rural women farmers sampled in this study were young in the age group between 20-35 years; predominantly on nuclear families; and from Hindu SC & ST and Hindu OBC households. WPR in agricultural activities fell as education levels rose. A significant portion of the female respondents worked in agriculture. It was shown that the age of the women and their ability to make decisions positively connected. It has been discovered that farm women's education has a positive impact on their participation in agricultural decision-making. Compared to SC and ST respondents, respondents from forward castes participated in farming decisions more frequently. Despite the fact that male farmers scored better on the decision-making scale, most decisions were made in collaboration with female participants, a sign of the rising social position of farming women.